Impact of microvariability on classification and management of peatlands in Asia - Padmanabhan, Eswaran; Hari, E.; Reich, P. (Universiti Malaysia Sarawak (UNIMAS), 2008)
Globally, wetlands occupy about 18.96 x 106 km2, of which 2% is made up of organic soils. In Asia, about 2.2 million km2 (~ 1.0%) of the land surface comprises peat or Histosols. The current global approach to agriculture places considerable emphasis on environmental quality, conservation of biodiversity and preservation of ecosystem while striving to achieve sustainable production in agroecosystems. In Asia, land use on the peatlands is low-input subsistence-based systems. In a few countries, such as Malaysia and Indonesia, rubber and oil-palm are cultivated on a plantation scale. Subsistence-based agricultural systems, understandably, would not be able to provide the level of input required for sustainable management of peat lands. The knowledge base for such systems is highly traditional in nature and is therefore vulnerable to the uncontrolled changes that occur in the evolution of the agro-ecosystem. Commercial-based agricultural systems appear to thrive in areas dominated by shallow peat. This system is technology-based, has a greater control over changes that may occur within the system but is perhaps still not in harmony with nature. Ignorance of the functions and value of such areas has lead to many forms of degradation. Therefore, sustainable development of the peat soils requires not only a holistic approach to the management but also dictates the need for a paradigm shift in resource characterization, research trends and land use policies.The paper elaborates on the paradigm shift in sustainable land management system and advocates a holistic approach wherein agronomic factors, environmental considerations as well as the much de-emphasized socioeconomic aspects, are all integrated into new research approaches. Research strategies needed to ensure sustainable agricultural development of organic soils include the urgent need for innovative measures to characterize the resource, evaluating and monitoring soil quality, assessing the potential of peat lands to release methane and other greenhouse gases upon drainage, and assessing the integrity of the ecosystem. Issues pertaining to productivity, assisting in the design of rational policies for development, promoting preservation of heritage, inculcating the ownership concept and developing better methods to gauge the economic viability of such projects are additional important factors that ensure sustainability. The most important factor differentiating peatlands from their mineral counterparts is microvariability; this, specifically in the context of small farms had not been addressed adequately and requires innovative approaches and technologies. Conventional soil surveys must be augmented with more innovative techniques as current methods suffer from various kinds of limitations.